Konsep Kafa’ah Maliyah Dalam Perkawinan Suku Bugis Pada Suku Jawa Perspektif Maslahah Mursalah : (Studi Kerukunan Keluarga Sulawesi Selatan) - Hafshah; Fakhruddin; Thoriquddin, Moh (Maqasid: Jurnal Studi Hukum Islam, 2025)
This article discusses the concept of kafa'ah maliyah (economic equality) in the context of inter-ethnic marriage between the Bugis and Javanese communities, focusing on the Kerukunan Keluarga Sulawesi Selatan (KKSS) community in Malang City. This study is motivated by differences in cultural views between the Bugis tribe who emphasize the importance of financial readiness, especially through the practice of "uang panai'", and the Javanese community who emphasize harmony and simplicity in marriage. This study uses a qualitative approach with a juridical-empirical method and a sociological approach. Data were obtained through interviews with members of the KKSS community and direct observation. The results of the study indicate that the concept of kafa'ah maliyah is still an important consideration in the Bugis community in the diaspora, but has undergone cultural adaptation when dealing with the Javanese community. From the perspective of maslahah mursalah, the application of kafa'ah maliyah is considered relevant as long as it does not cause difficulties and maintains the welfare of the household. This article concludes that economic equality remains an important aspect in maintaining household stability, especially in the context of intercultural marriage.